METACOGNITIVE AWARENESS COMPONENTS OF HIGH-ACADEMIC ABILITY STUDENTS IN BIOLOGY HYBRID LEARNING: PROFILE AND CORRELATION - Hindun, Iin; Nurwidodo, N.; Wicaksono, Azizul Ghofar Candra (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Metacognitive awareness has been considered as one of the factors within students that determines learning success. It can be developed through a hybrid learning approach. The purpose of this quantitative research was to examine the metacognitive awareness profile of students with high-academic ability in hybrid learning implementation. The subjects of this study were the students of XI-Science class of state senior high school of Malang. The Metacognitive Awareness Inventory was used as the data collection instrument, while descriptive statistics and Pearson Product-Moment were chosen as the data analysis techniques. The results of the study informed that the students? metacognitive awareness was divided into four categories, i.e. very good (9%), good (43%), enough (46%), and very low (2%). The three components of metacognitive awareness were classified as "enough", while the five components of students were categorized as "good". The eight metacognition components showed significant correlations each other (r > 0.41, n = 55, p < 0.01). It can be concluded that the majority of students? metacognitive awareness was satisfactory even though there were a small proportion of students whose metacognitive awareness was not good.